Analisis Penerapan Sistem dan Prosedur Pengeluaran Kas Belanja Langsung Pada Badan Perencanaan Pembangunan Daerah Provinsi Sulawesi Utara - Ismail, Adelia Virisya; Morasa, Jenny; Datu, Christian (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
The system and procedures for cash disbursement are crucial to be implemented effectively and effecienly in a regional government agency in accordance with the applicable regulations to prevent wasteful expenditure of the budget. Direct expenditure is a type of expenditure made by the work unit whose funds flow directly from the regional/state cash account to third parties or other parties that have been determined. The purpose of this study was to determine the application of the system and procedures for direct expenditure cash disbursements at the North Sulawesi Regional Development Planning Agency. The analysis method used is triangulation of data sources. The results showed that the implementation of direct expenditure cash disbursements system and procedures at the North Sulawesi Regional Development Planning Agency is in accordance with the Regulation of The Minister of Home Affairs (Permendagri) number 77 of 2020 concerning technical guidelines for regional financial management.